1997
DOI: 10.1029/97gl01608
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter's ionosphere: Results from the First Galileo Radio Occultation Experiment

Abstract: The Galileo spacecraft passed behind Jupiter on December 8, 1995, allowing the first radio occultation measurements of its ionospheric structure in 16 years. At ingress (24°S, 68°W), the principal peak of electron density is located at an altitude of 900 km above the 1‐bar pressure level, with a peak density of 105 cm−3 and a thickness of ∼200 km. At egress (43°S, 28°W), the main peak is centered near 2000 km altitude, with a peak density of 2×104 cm−3 and a thickness of ∼1000 km. Two thin layers, possibly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 23 publications
3
96
1
1
Order By: Relevance
“…It has been successfully used for many bodies in the solar system, including Jupiter and its satellites (Eshleman, 1975;Hinson et al, 1997), Saturn (Lindal et al, 1985), Uranus (Lindal et al, 1987), Neptune and Triton (Lindal, 1992), Mars (Cahoy et al, 2006), and Venus (Jenkins et al, 1994;Hinson and Jenkins, 1995). Prior to Cassini, the Voyager 1 spacecraft was occulted by Titan in 1979, early in Titan's northern spring (Lindal et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used for many bodies in the solar system, including Jupiter and its satellites (Eshleman, 1975;Hinson et al, 1997), Saturn (Lindal et al, 1985), Uranus (Lindal et al, 1987), Neptune and Triton (Lindal, 1992), Mars (Cahoy et al, 2006), and Venus (Jenkins et al, 1994;Hinson and Jenkins, 1995). Prior to Cassini, the Voyager 1 spacecraft was occulted by Titan in 1979, early in Titan's northern spring (Lindal et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Hinson et al [1997] reported on the peak electron density n e ≈ 10 5 cm −3 located at the altitude h m ≈ 900 km with thickness H ≈ 200 km in the evening sector, in the morning sector these parameters are n e ≈ 2×10 4 cm −3 , h m ≈ 2000 km, and H ≈ 1000 km. The directivity pattern of the Jovian decametric radiation source represents a hollow cone, which is magnetic field aligned and has an angular aperture 2θ s ≈ 120…”
Section: Propagation Of the Extraordinary Electromagnetic Wave In A Mmentioning
confidence: 99%
“…An example is the addition of radio occultation measurements and radio link budget estimations (Sect. 3.1), which is of particular interest for the planetary toolbox since such measurements are relevant for planetary exploration (e.g., Eshleman et al, 1987;Hinson et al, 1997;Oschlisniok et al, 2012). Some physical processes affect both passive and active measurements.…”
Section: Further New Model Features and Remaining Restrictionsmentioning
confidence: 99%